The Ability of Islamic Religious Education Study Program Students in Overcoming Academic Stress Problems at Universitas Islam Negeri Sumatera Utara Medan - Hasan Basri; Azmar Hidayat; Hilman Rizky Hasibuan; Zaizul Ab Rahman (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2025)
The high level of academic stress in students of the PAI Study Program at UIN Sumatra Utara Medan is caused by academic demands, social pressure, and family expectations. The data show a significant prevalence of academic stress globally (38-71%), Asia (39.6-61.3%), and Indonesia (36.7-71.6%). This academic stress negatively impacts students' concentration, problem-solving abilities, and academic performance, even though they have an advantage in faith-based coping strategies. This study aims to find out what are the factors that affect the academic stress of study program students and find out how PAI study program students in overcoming the problem of academic stress at the UIN Sumatra Utara Medan. This study uses quantitative descriptive research. This study uses the data collection method used is the questionnaire method. Questionnaires used by researchers as research instruments. The data was taken using a questionnaire to students to determine the level of academic stress in classroom learning. The results of this study show that there are two factors. Namely: the first factor when students can overcome academic stress by: sharing stories about the problems they are facing with peers, asking for moral support from friends, and sharing stories about the problems they are facing with parents. While the second factor when students overcome academic stress by: taking advantage of free time to do assignments, and immediately do assignments. The implications of this study show that the handling of academic stress in PAI students requires a comprehensive and integrated approach. The findings that students use a combination of social strategies (sharing stories with friends and parents, seeking moral support) and time management strategies (working on tasks immediately, making use of free time) provide important guidance for educational institutions to develop more effective support systems. Keywords: Academic; Student; Stress